2008
DOI: 10.1111/j.1468-3083.2008.02710.x
|View full text |Cite
|
Sign up to set email alerts
|

Ano‐genital granulomatosis treated with ciprofloxacin

Abstract: the location of human hair follicle stem cells. J Cell Sci 1998; 111: 3179 -3188. 4 Ohyama M, Terunuma A, Tock CL et al. Characterization and isolation of stem cell-enriched human hair follicle bulge cells. J Clin Invest 2006; 116: 249-260. 5 Ekmekci TR, Koslu A. Tufted hair folliculitis causing skullcap-pattern cicatricial alopecia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Furthermore, longterm metronidazole is associated with peripheral neuropathy, which can limit its continued use [13]. With the advent of biological agents, several studies have reported excellent outcomes with infliximab and azathioprine [3,4,[6][7][8][9][10][11][12][13][14][15] among others like ustekinumab, which have shown rapid resolution of symptoms similar to the outcome in our patient [15].…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Furthermore, longterm metronidazole is associated with peripheral neuropathy, which can limit its continued use [13]. With the advent of biological agents, several studies have reported excellent outcomes with infliximab and azathioprine [3,4,[6][7][8][9][10][11][12][13][14][15] among others like ustekinumab, which have shown rapid resolution of symptoms similar to the outcome in our patient [15].…”
Section: Discussionmentioning
confidence: 68%
“…Most studies suggest that a definitive diagnosis of Crohn’s disease is best made with a biopsy of the lesion, which shows non-caseating granulomas and chronic inflammatory change in the background [ 8 ]. Some studies have classified lesions with granulomas as vulval granulomatosis in the absence of Crohn’s disease [ 9 ]. However, having biopsy-confirmed diagnoses is not agreed upon.…”
Section: Discussionmentioning
confidence: 99%
“…If no evidence of Crohn's disease is found at that time, the disease can simply be labeled as anogenital granulomatosis. Treatment is similar regardless of the diagnosis as cutaneous Crohn's disease or anogenital granulomatosis of unknown origin [10].…”
Section: Discussionmentioning
confidence: 99%